THE DEVELOPMENT SCOPE AND PERSPECTIVES OF SOCIAL BONDS AS AN INNOVATIVE INSTRUMENT FOR FINANCING SOCIAL IMPACT - ANUFRIJEV, Ana; ANIČIĆ, Anđelka; GIZIEW, Almaz (Journal of process management and new technologies, 2025)
The paper analyzes the development, functioning mechanisms and prospects of social bonds as an innovative financial instrument aimed at achieving measurable social impact. Social bonds are based on a results-based financing model, in which private capital is mobilized for the implementation of projects of public importance, while the return on investment is paid only if predefined social outcomes are achieved. The paper discusses the key characteristics of social bonds, their advantages and limitations, with an analysis of international experiences and the implementation of different models. Special emphasis is placed on institutional prerequisites, the quality of performance measurement, the distribution of risks between actors and the importance of transparent evaluation. Through a review of available case studies, examples of the application of social bonds in the areas of employment of vulnerable groups, education, social protection and public health are presented. The findings suggest that social bonds can contribute to more efficient and sustainable financing of social policies, but their success depends on the regulatory framework, institutional capacity and the quality of available data. The paper provides a basis for assessing the feasibility of applying this instrument in developing countries and provides guidelines for future research.Keywords: Social bonds, innovative financial instruments, performance-based financing, social impact, public policies, sustainable financing, performance evaluation.
Keywords: Social bonds; innovative financial instruments; performance-based financing; social impact; public policies; sustainable financing; performance evaluation